Air-stable highly crystalline formamidinium perovskite 1D structures for ultrasensitive photodetectors - Chen, G. (2021)
State-of-the-art optoelectronic devices based on metal-halide perovskites demand solution-processed structures with high crystallinity, controlled crystallographic orientation, and enhanced environmental stability. Formamidinium lead iodide (α-FAPbI3) possesses a suitable bandgap of 1.48 eV and enhanced thermal stability, whereas perovskite-type polymorph (α-phase) is thermodynamically instable at ambient temperatures. Stable α-FAPbI3 perovskite 1D structure arrays with high crystallinity and ordered crystallographic orientation are developed by controlled nucleation and growth in capillary bridges. By surface functionalization with phenylethylammonium ions (PEA+), FAPbI3 wires sustain a stable α-phase after 28 day storage in the ambient environment with a relative humidity of 50%. Enhanced photoluminescence (PL) intensity and elongated PL lifetime demonstrate suppressed trap density and high crystallinity in these 1D structures, which is also reflected by the enhanced diffraction density and pure (001) crystallographic orientation in the grazing-incidence wide-angle X-ray scattering (GIWAXS) pattern. Based on these high-quality 1D structures, sensitive photodetectors are achieved with average responsivities of 5282 A W−1, average specific detectivities of more than 1.45 × 1014 Jones, and a fast response speed with a 3 dB bandwidth of 15 kHz.